Study on Advanced Treatment of Coking Wastewater by Fenton Process Improved With Coagulation-Response Surface Method - XU Weidong; ZHANG Fakui; LI Jie; WANG Yae; ZHENG Xuejun; DUAN Nan (Renmin Zhujiang)
After biochemical treatment of coking wastewater,the organic matter is difficult to reduce further.In order to meet the emission requirements,the effluent shall be subjected to an advanced treatment to reduce its organic matter.This paper treats the coking wastewater by the combined coagulation-Fenton method.The results show that:When the influent COD is 250~400 mg/L,the optimal coagulation conditions are as follows:coagulant PFS dosage:800 mg/L;pH:8;CPAM dosage:0 mg/L;and stirring time:15 min.The optimal conditions of Fenton are as below:Fe2+ dosage:302.38 mg/l;n(Fe2+)∶n(H2O2):1.00∶6.84;initial pH:3.84;reaction time:125.84 min.After the advanced treatment by coagulation-Fenton oxidation,the organic matter concentration decreases from 250~400 mg/L to 60 mg/L or below,and the effluent meets the Emission Standard of Pollutants for Coking Chemical Industry (GB 16171—2012).